Pendekatan Positive Narrative dalam Penulisan Naskah Animasi “Aku Jaga Tubuhku” Sebagai Media Literasi Perlindungan Diri Anak - Azmi Maharani; Encang Saepudin; Heru Ryanto Budiana (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
The number of cases of sexual violence against children in Indonesia remains alarming, particularly among elementary school-aged children. One factor contributing to children's high vulnerability is a lack of understanding of body boundaries and self-protection. Furthermore, education about the body and self-protection is often considered taboo, resulting in inadequate communication with children. This article discusses the application of a positive narrative approach in writing an educational animation script entitled